2003
DOI: 10.1046/j.1523-1755.2003.00212.x
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic differences and determinants of proteinuria among South Asian subgroups in Pakistan

Abstract: We conclude that unmeasured environmental or genetic factors account for ethnic variations in proteinuria, and deserve further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
2
17
2
Order By: Relevance
“…All independent predictors of proteinuria were retained in the final model. In addition, clinically important variables (systolic blood pressure) and those significantly associated with proteinuria (p<0.05) in the univariate analyses were forced in the models, and retained if they were significantly associated with proteinuria in the multivariate analyses [17]. Model fittings were tested in the final models by comparing the log likelihood ratios.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All independent predictors of proteinuria were retained in the final model. In addition, clinically important variables (systolic blood pressure) and those significantly associated with proteinuria (p<0.05) in the univariate analyses were forced in the models, and retained if they were significantly associated with proteinuria in the multivariate analyses [17]. Model fittings were tested in the final models by comparing the log likelihood ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Previously we reported differences among ethnic subgroups in the prevalence of proteinuria in the adult population of Pakistan, which could not be accounted for by the presence of hypertension, diabetes, and other sociodemographic risk factors [17]. The cause of ethnic variation in proteinuria in adults is not known.…”
Section: Introductionmentioning
confidence: 99%
“…equations with measured Ccr was not as good as reported in other populations, both equations performed better than serum creatinine. Although being reported for the first time, the alarmingly high prevalence of reduced GFR in adult men and women in Pakistan is not unexpected as the prevalence of risk factors of CKD including hypertension and diabetes is one of the highest reported worldwide (22). The National Health Survey of Pakistan (1990 to 1994) showed that one of three individuals aged 45 yr or older has hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from Pakistan (35) and South East Asia (36) demonstrate wide variations by ethnic subgroup in the prevalence of dipstick proteinuria. However, these studies do not have European comparators and do not provide evidence regarding determinants of micro-or macroalbuminuria in populations representative of our study group of first-generation migrants of largely Indian origin.…”
Section: Comparison With Other Studiesmentioning
confidence: 99%